Utilizing Social Media for Enhancing English Language Learning Among High School Students in Sungai Penuh - Husaini, Muhammad (Jurnal Aplikasi IPTEK Indonesia, 2021)
This research investigates the role of social media as a tool for enhancing English language learning among high school students in Sungai Penuh. With platforms like Instagram, YouTube, and TikTok widely accessible and popular among students, the study examines their effectiveness in promoting language practice, vocabulary development, and engagement outside the traditional classroom. Employing a qualitative approach, data were collected through interviews and focus group discussions with students from various high schools to understand their experiences and attitudes towards social media as a learning aid. Findings reveal that social media offers a dynamic, interactive environment that supports language acquisition, aligning learning with students’ daily activities. However, challenges such as distractions, the need for structured guidance, and content quality concerns were identified. The study suggests that with guided integration, social media holds potential to foster active and engaged language learning in the digital age